Effectiveness of emergency surgery for five common acute conditions: an instrumental variable analysis of a national routine database. (19th May 2022) - Hutchings, A.; O'Neill, S.; Lugo‐Palacios, D.; Moler Zapata, S.; Silverwood, R.; Cromwell, D.; Keele, L.; Bellingan, G.; Moonesinghe, S. R.; Smart, N.; Hinchliffe, R.; Grieve, R.
Summary: The effectiveness of emergency surgery vs. non‐emergency surgery strategies for emergency admissions with acute appendicitis, gallstone disease, diverticular disease, abdominal wall hernia or intestinal obstruction is unknown. Data on emergency admissions for adult patients from 2010 to 2019 at 175 acute National Health Service hospitals in England were extracted from the Hospital Episode Statistics database. Cohort sizes were: 268, 144 (appendicitis); 240, 977 (gallstone disease); 138, 869 (diverticular disease); 106, 432 (hernia); and 133, 073 (intestinal obstruction). The primary outcome was number of days alive and out of hospital at 90 days. The effectiveness of emergency surgery vs. non‐emergency surgery strategies was estimated using an instrumental variable design and is reported for the cohort and pre‐specified sub‐groups (age, sex, number of comorbidities and frailty level). Average days alive and out of hospital at 90 days for all five cohorts were similar, with the following mean differences (95%CI) for emergency surgery minus non‐emergency surgery after adjusting for confounding: −0.73 days (−2.10–0.64) for appendicitis; 0.60 (−0.10–1.30) for gallstone disease; −2.66 (−15.7–10.4) for diverticular disease; −0.07 (−2.40–2.25) for hernia; and 3.32 (−3.13–9.76) for intestinal obstruction. For patients with 'severe frailty', mean differences (95%CI) in days alive and out of hospital for emergency surgery were lower than for non‐emergency surgery strategies: −21.0 (−27.4 to −14.6) for appendicitis; −5.72 (−11.3 to −0.2) for gallstone disease, −38.9 (−63.3 to −14.6) for diverticular disease; −19.5 (−26.6 to −12.3) for hernia; and − 34.5 (−46.7 to −22.4) for intestinal obstruction. For patients without frailty, the mean differences (95%CI) in days alive and out of hospital were: −0.18 (−1.56–1.20) for appendicitis; 0.93 (0.48–1.39) for gallstone disease; 5.35 (−2.56–13.28) for diverticular disease; 2.26 (0.37–4.15) for hernia; and 18.2 (14.8–22.47) for intestinal obstruction. Emergency surgery and non‐emergency surgery strategies led to similar average days alive and out of hospital at 90 days for five acute conditions. The comparative effectiveness of emergency surgery and non‐emergency surgery strategies for these conditions may be modified by patient factors.